INSTAGRAM-ABLE ATAU LOYAL PERAN BRAND AWARENESS & BRAND IMAGE DALAM MENENTUKAN RE-USE INTENTIONS PENIKMAT KOPI - Shadiq, Muhammad Aththur; Erwin, Erwin; Chandra, Fernando Laurence; Tjan, Tjan; Poaler, Amelya (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to analyze the role of Instagram in enhancing marketing activities, particularly in shaping brand awareness, brand image, and driving Brand Instagram Re-usage Intentions (BIRI) within the coffee industry in Makassar. In the digital age dominated by social media, Instagram has emerged as a highly influential platform in digital marketing strategies. With its distinctive features, Instagram serves not only as a communication tool but also as a strategic platform to build and reinforce brand image and brand awareness. This research employs a descriptive quantitative approach using a survey method. Data were collected from 211 respondents who are active Instagram-using patrons of coffee shops in Makassar. The sampling technique used was purposive sampling with specific criteria. A 5-point Likert scale questionnaire was used as the research instrument to measure respondents' perceptions of the research variables. The collected data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the aid of WarpPLS 8.0 software. The results of the study indicate that Instagram Marketing Activities (IMA) have a positive and significant effect on BIRI, both directly and through the mediation of Brand Awareness (BA) and Brand Image (BI). This study makes a significant contribution to the development of digital marketing strategies, especially for those in the coffee industry seeking to leverage Instagram to enhance brand awareness, brand image, and customer loyalty. The findings of this study are expected to provide guidance for coffee industry players in designing effective marketing strategies through the Instagram platform.